Blood Pressure Drop and Penumbral Tissue Loss in Nonrecanalized Emergent Large Vessel Occlusion. Issue 10 (October 2019) - Jeong, Han-Gil; Kim, Beom Joon; Kim, Hyeran; Jung, Cheolkyu; Han, Moon-Ku; Liebeskind, David S.; Bae, Hee-Joon
Abstract : Background and Purpose—: For patients with emergent large vessel occlusion who may not benefit from timely recanalization treatment, maintaining adequate cerebral perfusion to prevent penumbral tissue loss is a key therapeutic strategy. Cerebral perfusion should be proportional to systemic blood pressure (BP) due to the loss of autoregulation properties in ischemic brain tissue. We hypothesized that acute fluctuations in BP would lead to aggravated penumbral tissue loss in persistent large vessel occlusion. Methods—: A total of 80 patients with persistent large vessel occlusion of internal carotid artery or middle cerebral artery admitted within 24 hours after onset, and with a baseline, National Institutes of Health Stroke Scale score ≥4-point were included. Baseline and follow-up (median 88 hours) magnetic resonance images were analyzed, and penumbra was defined as the Tmax >6 s region excluding baseline infarction. The hypoperfusion intensity ratio (Tmax >10 s/Tmax >6 s) was calculated within the penumbra. Penumbral tissue loss (%) was defined as the proportion of follow-up infarct in the penumbra. With serial BP measurements in the first 24 hours (median 29, interquartile range 26–35), BP and BP variability parameters, including BPdropmax (change from local maxima to minima), were calculated and compared. Generalized linear models were applied to examine the association between BP parameters and the penumbral tissue loss. Results—: The median penumbral volume was 79.3 mL (interquartile range, 38.2–129.6) and median penumbral tissue loss was 36.7% (interquartile range, 12.0–56.1). In a multivariable analysis, systolic BP (SBP) SBPdropmax (β±SE of fourth quartile, 17.82±6.58; P value, 0.01) and diastolic BP (DBP) DBPdropmax (β±SE of fourth quartile, 14.04±6.38; P value, 0.01) were associated with increasing penumbral tissue loss, independently of age, baseline infarction and hypoperfusion intensity ratio. DBPincmax, SBPmax, DBPmax, SBPmax-min, DBPmax-min, and most of the DBP variability indices were associated with penumbral tissue loss. Conclusions—: BP fluctuations, even a brief and drastic BP drop in the first 24 hours, significantly contributed to penumbral tissue loss irrespective of baseline hypoperfusion. Abstract : Supplemental Digital Content is available in the text.